TT 414 revisited: New Results about Forgotten Finds from the Asasif/Thebes Based on the 2018 and 2019 Seasons of the Ankh-Hor Project - Budka, Julia (Ägypten und Levante, 2020)
Neglected finds, first of all, wooden coffins from the 26th Dynasty to Roman times, discovered during the Austrian excavations of the tomb of Ankh-Hor in Asasif (TT 414), are currently being studied by the new Ankh-Hor Project hosted at the LMU Munich. The project aims at reconstructing the complete history of the usage of the tomb and its multiple tomb groups, focusing on coffins as the prime evidence. The most important results from the 2018 and 2019 seasons regarding the large corpus of coffins from TT 414 are summarized and future work is outlined.